Basics of Imposing Punishment in the Form of Compulsory Community Service and Their Improvement - Rakhimbaevich, Kuchkarov Turgun (Indonesian Journal Publisher, 2024)
In this article, the author discusses the legal basis of imposing a sentence in the form of mandatory community service, the criminal law norms of this type of punishment, in particular the imposition of a lighter sentence, the imposition of a punishment when the guilty person is actually remorseful for his actions, the imposition of punishment for incomplete and complicit crimes, the commission of several crimes Aspects related to the manner in which the norms can be applied, such as the imposition of punishment for several convictions, have been thoroughly analyzed. At the same time, the author put forward his proposals for the improvement of norms related to the imposition of mandatory community service punishment and its execution.